Assessing Forest Fire Risk in Indonesia with the Canadian Forest Fire Weather Index System (CFFWIS) - Sulle, Yusuf; Setianingsih, Casi; Dinimaharawati, Ashri (eProceedings of Engineering, 2024)
The extensive forested areas, while precious, play a role in the heightened occurrence of forest fires, resultingfrom a combination of human actions and natural factors. Themain catalyst is frequently deliberate human activities associated with land clearance, unintentionally amplifying thevulnerability to fires. This study centers on assessing forest firerisk using the Fire Weather Index (FWI), derived from four parameters: Temperature, Humidity, Wind, and Rainfall,obtained from Indonesia's BMKG. The FWI results are analyzed in relation to real-world events, gathered from diversesources, including news, to evaluate their efficacy. This research aims to address the challenge of forest fire management in thecontext of Indonesia's unique ecosystem, utilizing the FWI to enhance preparedness and response strategies. Keyword: Forest Fires, Fire Weather Index, Climate Data, Indonesia, BMKG